2021
DOI: 10.4049/jimmunol.2000957
|View full text |Cite
|
Sign up to set email alerts
|

IL-27/IL-27R Mediates Protective Immunity against Chlamydial Infection by Suppressing Excessive Th17 Responses and Reducing Neutrophil Inflammation

Abstract: IL-27, a heterodimeric cytokine of the IL-12 family, has diverse influences on the development of multiple inflammatory diseases. In this study, we identified the protective role of IL-27/IL-27R in host defense against Chlamydia muridarum respiratory infection and further investigated the immunological mechanism. Our results showed that IL-27 was involved in C. muridarum infection and that IL-27R knockout mice (WSX-1–/– mice) suffered more severe disease, with greater body weight loss, higher chlamydial loads,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…To determine the participation of FcγRI in chlamydial infection, we employed our established model of chlamydial respiratory infection by intranasal injection of C. muridarum into C57 BL/6 mice as previously described [ 10 , 16 ]. As the 3 days post-infection (3 d p.i.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the participation of FcγRI in chlamydial infection, we employed our established model of chlamydial respiratory infection by intranasal injection of C. muridarum into C57 BL/6 mice as previously described [ 10 , 16 ]. As the 3 days post-infection (3 d p.i.…”
Section: Resultsmentioning
confidence: 99%
“…For histopathological analyses, C. muridarum -infected lung tissues were fixed in 4% paraformaldehyde (PFA) (Life-iLab, Shanghai, China) and routinely embedded in paraffin, sectioned (5 μm), and stained with hematoxylin and eosin (H&E) according to the manufacturer’s instructions (Solarbio). The pathological changes were evaluated by the semi-quantitative histology score in a blinded manner as described previously [ 16 ]. Briefly, the inflammatory grades were scored as: score 0, normal; score 1, moderate and limited inflammatory granuloma with less than 25% cell infiltration and no obvious infiltration in adjacent alveolar septa or air space; score 2, moderate interstitial pneumonia with 25–50% cell infiltration and septal congestion and septal edema; score 3, inflammatory cells infiltrated into perivascular, peribronchiolar, alveolar septa and air space, accounting for 50–75% of the area; score 4, over 75% of the lung area infiltrated with inflammatory cells.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the double-bladed sword impact of IL-17 on host defense against C. muridarum respiratory infection was reported by our previous studies, Bai et al firstly demonstrated that moderate IL-17/Th17 response promoted protective type 1 T cell immunity by modulating DC function [ 43 ]. However, Zha et al founded that excessive IL-17/Th17 response caused increased neutrophil inflammation and contributed to severer disease when IL-27R deficient [ 26 ]. In this model, the inconsistency between higher IL-17 production and reduced neutrophil recruitment could be explained by the diversity of neutrophil chemotactic factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, persistent robust effector functions may also lead to neutrophil-mediated tissue damages at infected sites [ 21 ], suggesting the dual role of neutrophils in inflammation. In chlamydial infection, the role of neutrophils in chlamydia-induced pathology has been revealed [ 22 26 ]. Using the plasmid-deficient strain of C. muridarum , Frazer et al found that enhanced neutrophil longevity and recruitment contributed to the severity of oviduct pathology [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation